Outcomes with FOLFIRINOX for borderline resectable and locally unresectable pancreatic cancer. Issue 4 (16th August 2013) - Boone, Brian A.; Steve, Jennifer; Krasinskas, Alyssa M.; Zureikat, Amer H.; Lembersky, Barry C.; Gibson, Michael K.; Stoller, Ronald G.; Zeh, Herbert J.; Bahary, Nathan
Abstract Background Trials examining FOLFIRINOX in metastatic pancreatic cancer demonstrate higher response rates compared to gemcitabine‐based regimens. There is currently limited experience with neoadjuvant FOLFIRINOX in pancreatic cancer. Methods Retrospective review of outcomes of patients with borderline resectable or locally unresectable pancreatic cancer who were recommended to undergo neoadjuvant treatment with FOLFIRINOX. Results FOLFIRINOX was recommended for 25 patients with pancreatic cancer, 13 (52%) unresectable and 12 (48%) borderline resectable. Four patients (16%) refused treatment or were lost to follow‐up. Twenty‐one patients (84%) were treated with a median of 4.7 cycles. Six patients (29%) required dose reductions secondary to toxicity. Two patients (9%) were unable to tolerate treatment and three patients (14%) had disease progression on treatment. Seven patients (33%) underwent surgical resection following treatment with FOLFIRINOX alone, 2 (10%) of which were initially unresectable. Two patients underwent resection following FOLFIRINOX + stereotactic body radiation therapy (SBRT). The R0 resection rate for patients treated with FOLFIRINOX ± SBRT was 33% (55% borderline resectable, 10% unresectable). A total of five patients (24%) demonstrated a significant pathologic response. Conclusions FOLFIRINOX is a biologically active regimen in borderline resectable and locally unresectable pancreatic cancer with encouraging R0 resection and pathologic response rates. J. Surg. Oncol. 2013 108:236–241. © 2013 Wiley Periodicals, Inc.